The significance of T129C and G2677T polymorphism of the MDR1 gene in ovarian cancer patients - Kufelnicka-Babout, Maja; Smolarz, Beata; Kulig, Andrzej; Szpakowski, Marian; Wilczyński, Jacek R. (Menopause Review/Przegląd Menopauzalny, 2008)
Aim of the study: Despite advanced diagnostic and therapeutic procedures ovarian cancer is still responsible for high morbidity and mortality of women. As the effective screening has not been found yet, genetic approach seems to be justified to identify high-risk subjects. Single nucleotide polymorphisms (SNPs) are responsible for functional changes of multidrug resistance-1 ( MDR1 ) gene product glycoprotein P (P-gp), which could negatively influence its protective role against xenobiotics, thus increasing the risk of diseases, including cancer. In this study the T129C and G2677T polimorphisms were investiagated. Material and methods: The genotypes of T129C and G2677T polymorphism were determined by PCR-RFLP methods in 56 ovarian cancer subjects and 58 healthy women. Results: The distribution of genotypes for G2677T SNP in ovarian cancer patients vs. controls was: 10.7% vs. 53.45% for GG, 41.07% vs. 27.59% for GT and 48.21% vs. 18.97% for TT. For T129C polymorphism TT, TC and CC genotype frequencies in ovarian cancer patients were 46.1%, 30.8% and 23.1%, while in the control group 37.9%, 50% and 12,1% respectively. There were significant differences in the frequencies of alleles between the ovarian cancer subjects and controls for G2677T SNP (p<0.001), but no difference in the frequencies of alleles between the ovarian cancer subjects and the controls for T129C SNP has been found. Conclusions: The results of the current study provide evidence that the G2677T polymorphism of MDR1 may be linked to the appearance and development of ovarian cancer, but further research, conducted on a larger population, is needed to clarify this point.